Buccal Fat Pad in Intraoral Defect Reconstruction - Bither, Saurab (Springer India, 2011)
The use of buccal fat pad as a graft for intraoral defects is an uncommonly reported procedure but, it has been frequently used for closure of oro-antral and oro-nasal communications. Buccal fat pad was used to reconstruct 3 medium sized defects due to tumoral resection and oro-antral communication. It was used as an unlined pedicled graft. Three cases are discussed along with anatomical aspect of the buccal fat pad. The findings support the view that the buccal fat pad is versatile, logical, convenient, and reliable method for the reconstruction of oral defects up to 4–5 cm in diameter and it healed within 4–5 weeks.